Diagnosing boundary-layer fractional cloudiness in a mesoscale model - Mocko, David M., author (Colorado State University. Libraries, 1994)
The Regional Atmospheric Modeling System (RAMS), developed at Colorado State University, was used to predict boundary-layer clouds and diagnose fractional cloudiness. The case study for this project occurred on 7 July 1987 off the coast of southern California. On this day, a transition in the type of boundary-layer cloud was observed from a clear area, to an area of small scattered cumulus, to an area of broken stratocumulus, to an area of solid stratocumulus. This case study occurred during the First ISCCP (International Satellite Cloud Climatology Project) Regional Experiment (FIRE) field study in this locale. RAMS was configured with three interactive nested grids: a coarse grid with 80 km model spacing covering the western 1/4 of the U.S. and the eastern 1/3 of the Pacific, a 20 km grid covering the ocean waters off the southern California coast, and a 5 km grid covering the transition area. The non-hydrostatic version of RAMS was chosen, and explicit bulk microphysics was used. The model was initialized using rawinsondes and surface aviation observations (SAOs) as archived at the National Center for Atmospheric Research (NCAR). A unique feature of this study is that a cumulus parameterization scheme was used that predicts on vertical velocity variance. Various fractional cloudiness schemes found in the literature were then implemented into RAMS and tested against each other in order to determine which best represented observed conditions. The RAMS model was also configured for a separate case study which occurred as part of the Boundary Layer Experiment - 1983 (BLX83). This field project took place over central Oklahoma in June of 1983. On the case day, clear conditions existed early in the morning. As the day progressed, scattered boundary-layer cumuli developed and dissipated through the afternoon. The model was configured with one 5 km grid and was initialized horizontally homogeneous with a morning sounding. The fractional cloudiness schemes were also examined for this case study and compared to observations.
April 5, 1994.
Also issued as author's thesis (M.S.) -- Colorado State University, 1994.
Keywords: Boundary layer (Meteorology); Cloudiness